Experimental investigation at CATANA facility of n-10B and p-11B reactions for the enhancement of proton therapy. (September 2021) - Mazzucconi, D.; Bortot, D.; Pola, A.; Fazzi, A.; Cazzola, L.; Conte, V.; Cirrone, G.A.P.; Petringa, G.; Cuttone, G.; Manti, L.; Agosteo, S.
Highlights: Study of the p- 11 B and n- 10 B reactions for the enhancement of protontherapy. Irradiation of a double-stage silicon telescope coupled to different boron targets at the CATANA protontherapy facility. Discrimination between alpha particles originated by thermal neutrons on 10 B from the ones produced by protons on 11 B. Abstract: The aim of the NEPTUNE (Nuclear process-driven Enhancement of Proton Therapy UNravEled) project is to investigate in detail both the physical and radiobiological phenomena that could justify an increase of the proton-induced cytogenetic effects in cells irradiated in presence of an agent containing natural boron. In this work, a double-stage silicon telescope coupled to different boron converters was irradiated at the CATANA proton therapy facility (INFN-LNS) for studying the proton boron fusion and the neutron boron capture reactions by discriminating secondary particles from primary protons. Different boron targets were developed by depositing boric acid, enriched with a higher than 99% content of 10 B or 11 B, on a 50 µm thick PolyMethilMetacrylate (PMMA) substrate. The 10 B target allows to evaluate the contribution of lithium and alpha particles produced by the boron neutron capture reaction triggered by secondary thermal neutrons, while the 11 B target is exploited for studying the effect of the p + 11 B → 3α nuclear reaction directly triggered by primary protons. Experimental results clearly show the presence of alpha particles from both the reactions. The silicon telescope is capable of discriminating, by means of the so-called "scatter plots", the contribution of alpha particles originated by thermal neutrons on 10 B with respect to the ones produced by protons impinging on 11 B. Although a reliable quantitative study of the alpha production rate has not been achieved yet, this work demonstrates that low energy and, therefore, high-LET particles from both the reactions can be measured.